MODEL PEMBELAJARAN KOOPERATIF TERHADAP KEMAMPUAN PASSING BAWAH PADA PERMAINAN BOLA VOLI SISWA KELAS VII SMP YAPIS CABANG TIMIKA - Petrosina Dokainubun (SATRIA : Journal of Sports Athleticism in Teaching and Recreation on Interdisciplinary Analysis, 2022)
This study aims to: 1) To determine the relationship between arm muscle strength and lower serve ability in volleyball games for Class VII students of Adventist Middle School Timika, 2) To determine the relationship between balance and lower serve ability in volleyball games of Class VII students of Adventist Middle School Timika. , 3) To find out the relationship between arm muscle strength and balance on the ability to serve down in volleyball for the seventh grade students of the Timika Adventist Junior High School. This research is a correlational study. The population in this study were all seventh grade students of Timika Adventist Middle School. The research sample was taken using simple random sampling method so that the number of samples obtained was 30 people. The results of this study indicate that: 1) There is a significant relationship between arm muscle strength and the ability to serve down in volleyball for seventh graders at Adventist Junior High School Timika with rxy (count) = 0.864 > r table = 0.374, 2) There is a significant relationship between balance on the ability to serve down in volleyball for seventh grade students of SMP Advent Timika with a value of rxy (count) = 0.515 > r table = 0.374, 3) There is a significant relationship between arm muscle strength and balance on the ability to serve down in volleyball games Class VII students of Adventist Middle School Timika with a value of rxy (count) = 0.881 > r table = 0.423